(untitled) (Redwood City, Calif., 1993)
This book introduce extensions to the relational data model. Other data models: a temporal model and query language for EER databases, a uniform model for temporal and versioned object-oriented databases...
Keywords: Cơ sở dữ liệu tạm thời,Temporal databases